Potential Correlation between Gene Mutations and Metabolic Changes in Acute Myeloid Leukemia - Jiang, Aili; Hou, Zhiying; Yu, Bingyan; Wang, Ning; Zhang, Bin (Natural Products Journal, The, 2024)
Acute myeloid leukemia (AML) is a common type of leukemia. However, the understanding of AML remains insufficient. The pathological progression of AML is closely related to chromosome abnormalities and genetic mutations. Gene mutation is an important factor in the pathogenesis of AML and a potential cause of drug resistance. Recent studies have shown that gene mutations in AML can cause metabolic changes. Metabolites, as downstream products of human physiological activities, can amplify physiological and disease-related signals. Therefore, the analysis of metabolite markers related to gene mutations can be used for early prediction of the occurrence of the disease. This review describes the types and significance of AML gene mutations and analyzes the characteristics of metabolic changes related to gene mutations.
Keywords: metabolomics